2004
DOI: 10.1016/j.physleta.2004.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Bell's inequality violation for continuous variable systems

Abstract: Two mode squeezed vacuum states allow Bell's inequality violation (BIQV) for all non-vanishing squeezing parameter (ζ). Maximal violation occurs at ζ → ∞ when the parity of either component averages to zero. For a given entangled two spin system BIQV is optimized via orientations of the operators entering the Bell operator (cf. S. L. Braunstein, A. Mann and M. Revzen: Phys. Rev. Lett. 68, 3259 (1992)). We show that for finite ζ in continuous variable systems (and in general whenever the dimensionality of the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 14 publications
(22 reference statements)
4
59
0
Order By: Relevance
“…[14] can be seen as extending those in Ref. [15][16][17][18][19] which all showed that ͉NOPA͘ violated Bell inequalities based on measuring photon-number parity (oddness or evenness). In terms of binary representations, these other papers violated Bell inequalities involving the values of the least significant bits (and not any other bits as in Ref.…”
Section: ͓14͔supporting
confidence: 69%
See 1 more Smart Citation
“…[14] can be seen as extending those in Ref. [15][16][17][18][19] which all showed that ͉NOPA͘ violated Bell inequalities based on measuring photon-number parity (oddness or evenness). In terms of binary representations, these other papers violated Bell inequalities involving the values of the least significant bits (and not any other bits as in Ref.…”
Section: ͓14͔supporting
confidence: 69%
“…Previous work [14][15][16][17][18][19] has shown that the state ͉NOPA͘ violates instances of the CHSH inequality with the maximum violation being 2 ͱ 2 [14,18,19]. The violations in Ref.…”
Section: A Least Significant Bitsmentioning
confidence: 97%
“…(93) we should choose a specific representation of the pseudospin operators; note that, as pointed out in Refs. [37,38], the violation of Bell inequalities for continuous variable systems depends, besides on the orientational parameters, on the chosen representation, since different S k leads to different expectation values of B PS . Here we consider the pseudospin operators corresponding to the Wigner functions [37] …”
Section: Nonlocality and Pseudospin Testmentioning
confidence: 99%
“…Different in form representations of the commutation relations presented above have been given in the recent literature [10,13,14]. It is well known that the phase-space shift of an observable can be implemented with the help of the local displacement operator D(q, p) that is familiar from the theory of coherent states.…”
Section: Bounded Observablesmentioning
confidence: 99%